The improvement effect of apple cider vinegar as a functional food on anthropometric indices, blood glucose and lipid profile in diabetic patients: a randomized controlled clinical trial - Jafarirad, Sima; Elahi, Mohammad-Reza; Mansoori, Anahita; Khanzadeh, Abdollah; Haghighizadeh, Mohammad-Hossein (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Numerous medical costs are spent each year on treating and preventing the progression of diabetes. The positive effect of apple cider vinegar (ACV) has been shown on post-prandial hyperglycemia. This study aimed to evaluate the effects of prolonged consumption of ACV on blood glucose indices and lipid profile in patients with type 2 diabetes. Methods This study was a randomized clinical trial and the participants were adults with type 2 diabetes. Participants were divided into two groups: ACV and control. The ACV group was treated with 30 ml of ACV per day. Both the intervention and control groups received the same recommendation for a healthy diet. Before and after eight weeks, fasting blood glucose, insulin, hemoglobin A1C, insulin resistance, total cholesterol (Chol), low-density lipoprotein (LDL), high-density lipoprotein (HDL) and triglyceride were measured. Results Fasting blood glucose decreased after intervention in both groups, which was only significant in the ACV group (p = 0.01). There was a significant difference in hemoglobin A1C levels between the two groups (p < 0.001) after eight weeks. LDL was decreased in the ACV group (p < 0.001). Total Chol, LDL/HDL and Chol/HDL ratio decreased after the intervention period in the ACV group compared to the control group (p = 0.003, p = 0.001 and p = 0.001, respectively). Conclusion Daily consumption of ACV may have beneficial effects in controlling blood glucose indices and lipid profile in patients with type 2 diabetes. Clinical trial registration http://www.irct.ir, identifier IRCT20140107016123N13.